The role of investment for poverty alleviation in Yogyakarta: Evidence from logit regression - Suripto, Suripto; Sukarniati, Lestari; Khasanah, Uswatun; Kurniawan, Mahrus Lutfi Adi; Istanti, Istanti (Universitas Muhammadiyah Yogyakarta, 2024)
This article discusses the Solow-Romet theory of economic growth, aiming to explain the relationship between household poverty in the Province of Daerah Istimewa Yogyakarta (DIY) through investments in education, quality of life improvement, and health. The study examines various influence variables, including Non-Formal Education (XNF), Educational Scholarships (XBS), Protein Consumption (PK), Disease Prevention Costs (XL), Calorie Consumption (IK)), Health Insurance Variables (XAS ), and Food Security (XT) in assessing the poverty status of households in the Special Region of Yogyakarta in 2021. The estimation model employs a logit mode approach, using data from Susenas (National Socioeconomic) data for the Special Province of Yogyakarta, with a sample size of 4044 households. The findings of this study indicate that investments in non-formal education, school fees, and educational scholarships do not significantly affect family poverty status. However, increased investment in quality of life (such as calorie consumption) and health (including disease prevention and health insurance spending) will affect the poverty status of households in the Special Province of Yogyakarta in 2021.